2013
DOI: 10.1158/1078-0432.ccr-13-0943
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preclinical Characterization of a Humanized Antibody Targeting CXCL12

Abstract: Purpose: Our goal was to develop a potent humanized antibody against mouse/human CXCL12. This report summarized its in vitro and in vivo activities.Experimental Design: Cell surface binding and cell migration assays were used to select neutralizing hamster antibodies, followed by testing in several animal models. Monoclonal antibody (mAb) 30D8 was selected for humanization based on its in vitro and in vivo activities.Results: 30D8, a hamster antibody against mouse and human CXCL12a, CXCL12b, and CXCL12g, was s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…For instance, CVX15 binding induces structural reconfiguration in the base of the receptor N-terminus as well as the extracellular regions of the helices. The binding interaction of CXCL12 to CXCR4 takes place with the RFFESH loop of CXCL12α interacting with the N-terminus of CXCR4, while the N-terminus of CXCL12 simultaneously interacts with the binding pocket comprising the transmembrane helices and the extracellular loops (Zhong et al, 2013). While this study has shed more light on CXCR4–ligand interactions, the observed variability in binding modes has further complicated the rationale design and predictability of essential structural backbones necessary for production of high-affinity CXCR4 binding ligands.…”
Section: Cxcr4 Antagonists As Therapeutic and Imaging Agentsmentioning
confidence: 99%
“…For instance, CVX15 binding induces structural reconfiguration in the base of the receptor N-terminus as well as the extracellular regions of the helices. The binding interaction of CXCL12 to CXCR4 takes place with the RFFESH loop of CXCL12α interacting with the N-terminus of CXCR4, while the N-terminus of CXCL12 simultaneously interacts with the binding pocket comprising the transmembrane helices and the extracellular loops (Zhong et al, 2013). While this study has shed more light on CXCR4–ligand interactions, the observed variability in binding modes has further complicated the rationale design and predictability of essential structural backbones necessary for production of high-affinity CXCR4 binding ligands.…”
Section: Cxcr4 Antagonists As Therapeutic and Imaging Agentsmentioning
confidence: 99%
“…Mogamulizumab, a monoclonal antibody targeting CCR4, recently became the first biologic to be approved for cutaneous T-cell lymphoma (33). In a complementary effort, antibodies (7, 148) and therapeutic nucleotides (35, 53, 95) are pursued as agents targeting chemokines. With all of these agents, oral availability is out of question; however, various approaches to improving metabolic stability have been successful (18, 95).…”
Section: On Druggability Of Chemokine Receptorsmentioning
confidence: 99%
“…Several CK-directed (CCL2, CCL5, and CXCL10) antibodies have been generated and tested in phase I/II clinical trials (Klarenbeek et al, 2012) in both cancer and inflammatory diseases. 30D8, a humanized antibody against mouse/human CXCL12, inhibits tumor growth and/or metastasis and improve arthritis in experimental in vitro and in vivo models (Zhong et al, 2013). However, the majority of antibodies that successfully entered clinical trials, targets CK receptors rather than ligands.…”
Section: Targeting Cxcl12–cxcr4/cxcr7 Axis In Cancer: Rationalementioning
confidence: 99%